2019
DOI: 10.1177/0892705719882977
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties, characterization, and preparation of composite materials containing a polymethacrylate with α-naphthyl side group and nanographene fillers

Abstract: 2-(Naphthalene-1-yl oxy)-2-oxoethyl methacrylate (NOEMA) was synthesized from reaction of naphthalene-1-yl 2-chloroacetate and sodium methacrylate and its homopolymer was prepared by free-radical polymerization method at 60°C. The glass transition temperature of pure poly(NOEMA) was estimated as 102°C by differential scanning calorimetry technique, whereas that of poly(NOEMA) containing 10 wt% nanographene was 83°C. While pure poly(NOEMA) from thermogravimetric analysis measurements was indicating a decomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Studies have reported that in the graphene‐doped polymer, mini‐capacitors are formed in the polymer matrix and an increase in the dielectric constants of graphene‐based polymer composites. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that in the graphene‐doped polymer, mini‐capacitors are formed in the polymer matrix and an increase in the dielectric constants of graphene‐based polymer composites. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that in the graphene-doped polymer, minicapacitors are formed in the polymer matrix and an increase in the dielectric constants of graphene-based polymer composites. [8] Insulation, in loud voltage applications, it is the most significant part of preventing the flow of current in undesirable ways. Dielectric and electric fields are essential properties for insulating materials.…”
Section: Introductionmentioning
confidence: 99%